DUKUNGAN KELUARGA MENINGKATKAN KEPATUHAN PASIEN DALAM MENGONSUMSI OBAT HIPERTENSI DI WILAYAH KERJA PUSKESMAS LIMBOTO BARAT - Rosmin Ilham; Fadli Syamsuddin; Adela Delia Tamrin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension drugs can reduce the symptoms of hypertension, but there are still many elderly people with hypertension who do not comply with taking drugs, this can be influenced by various factors including family support. The purpose of the study was to determine family support in improving patient adherence to taking hypertension drugs in the West Limboto Health Center Working Area. Descriptive quantitative research design. The total population of hypertensive patients who participated in the prolanis in August 2022 was 77 people. The sample totaled 77 people with total sampling technique. The instrument used is a family support questionnaire. Test statistics using analyze descriptive statistics. The results obtained by the family support of the emotional aspect of the majority were good at 76.6%, the majority award aspect was good at 74%, the information aspect was majority good at 77.9% and the instrumental aspect was majority good at 75.3%. It is concluded that family support in the elderly with hypertension is mostly good in emotional, informational, rewarding and instrumental aspects